Отримання трансгенних рослин арахісу (Arachis hypogaea L.) з генами білків-стимуляторів імунної відповіді проти туберкульозу AG85, ESAT6 - Ніфантова, С.М.; Комарницький, І.К.; Симоненко, Ю.В.; Кучук, М.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. The production of peanut cultivars with new properties is necessary.The purpose of this work was to develop a
method of transgenesis Ag85, ESAT6 genes in peanut genome by Agrobacterium-mediated transformation. Methods.
Transformation of peanut lines was carried out using cocultivation of peanut explants with Agrobacterium tumefaciens
strain GV3101 carrying genetic construct pCB064 containing Ag85, ESAT6 genes and nptII gene. Selection was held on
the solidified callus inducing medium with 100 mg/l kanamicyne. The selected callus clones were put on the regeneration
medium. Obtained regeneration lines were analysed using PCR-analysis and Western-blot analysis. Results. 8 peanut
regeneration lines had positive signals after PCR analysis with DNA fragments of required molecular size for nptII gene,
Ag85 and ESAT6 genes. 1 regeneration line of peanut had positive signals after Western-blot analysis. Conclusions.
Transgenic peanut plants containing Ag85, ESAT6 genes were obtained. We have developed transgenic peanut plants
expressing the Ag85, ESAT6 proteine.
Keywords: peanut, Ag85, ESAT6 genes, transformation.